The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.jasms.2005.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of binding affinity of protein-mutant dna complexes in solution by laser spray mass spectrometry

Abstract: We have applied laser spray mass spectrometry developed by Hiraoka et al. to investigate the binding affinity of protein-mutant DNA complexes. The results were compared with our previous data of collision-induced dissociation (CID) experiments using electrospray ionization mass spectrometry (ESI-MS). Systematic experiments were carried out on the complexes of the c-Myb DNA binding domain (c-Myb DBD) bound to eight kinds of 16-or 22-mer point mutant double-stranded DNA (dsDNA), whose solution K d values are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…This indicates that the laser heating seems less effective than lowering the pH of aqueous solution for the denaturation of this protein under the present experimental conditions. In other words, laser spray enables observation of the intermediate transition states of proteins in an appropriate buffer 17–20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the laser heating seems less effective than lowering the pH of aqueous solution for the denaturation of this protein under the present experimental conditions. In other words, laser spray enables observation of the intermediate transition states of proteins in an appropriate buffer 17–20…”
Section: Resultsmentioning
confidence: 99%
“…The general experimental procedures are similar to those described previously 17–20. In brief, a stainless steel capillary (i.d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okashi et al (2005) evaluated the binding affinity of complexes between a DNA-binding domain of the transcription factor c-MYB and several double-stranded DNA by electrospray ionization mass spectrometry; K D values in the range of 6.3×10 −7 M to 2.8×10 −9 M, similar to those obtained by us (10 −9 M) were found. Besides, other groups already calculated K D values for MYB proteins using several techniques, ranging from 4.5×10 −9 M (pNgTRF1, a doublestranded telomeric repeat binding factor with a single MYBlike domain of Nicotiana glutinosa, Yang et al 2003); 3.2× 10 −9 M (human TRF1, König et al 1998); 5.5× l0 −7 M using fluorescence anisotropy (Madan et al 1994); 8.0×10 −8 M (confirmed by ITC experiments for Tay1 protein from the yeast Yarrowia lipolytica containing two MYB domains), and 2.8×10 −9 M to 6.3×10 −7 M using mass spectrometry (Shi et al 2006). All these findings confirm that the binding affinity of MYB domains and DNA are clearly around 10 −8 M.…”
Section: Resultsmentioning
confidence: 89%
“…Many of the previously reported preparations have involved SDS PAGE to assess the size forms, which can both break apart larger Aβ assemblies and cause monomeric Aβ to aggregate ex vivo 42 . A highly cited previous report 23 used size exclusion chromatography to assess the size of the soluble Aβ aggregates, but the running buffer was ammonium acetate pH 8.5 which can cause changes in assembly of protein complexes [43][44][45][46][47] . We found that ammonium acetate pH 8.5 consistently changes the apparent size of soluble Aβ aggregates ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%